Congenital deformity of the paw in a captive tiger: case report - Rahal, Sheila C. [UNESP]; Volpi, Reinaldo S. [UNESP]; Teixeira, Carlos R. [UNESP]; Machado, Vania M. V. [UNESP]; Soares, Guilherme D. P. [UNESP]; Ramires Neto, Carlos [UNESP]; Linn, Kathleen (Biomed Central Ltd., 2012)
Background: The aim of this report was to describe the clinical signs, diagnostic approach, treatment and outcome in the case of a tiger with a deformity of the paw.Case presentation: A 1.5-year-old tiger (Panthera tigris) was presented with lameness of the left thoracic limb. A deformity involving the first and second metacarpal bones, and a soft tissue separation between the second and third metacarpal bones of the left front paw were observed. The second digit constantly struck the ground during locomotion. Based on the physical and radiographic evaluations, a diagnosis of ectrodactyly was made. A soft tissue reconstruction of the cleft with excision of both the second digit and distal portion of the second metacarpal bone was performed. Marked improvement of the locomotion was observed after surgical treatment, although the tiger showed a low degree of lameness probably associated with the discrepancy in length between the thoracic limbs.Conclusion: This report shows a rare deformity in an exotic feline that it is compatible to ectrodactyly. Reconstructive surgery of the cleft resulted in significant improvement of limb function.